Arts education in action : collaborative pedagogies for social justice - Travis, Sarah, 1979-; Stokes-Casey, Jody; Kim, Seoyeon (Common threads (University of Illinois (System). Press), 2020)
Arts educators have adopted social justice themes as part of a larger vision of transforming society. Social justice arts education confronts oppression and inequality arising from factors related to race, ethnicity, nationality, religion, class, ability, gender, and sexuality. This edition of Common Threads investigates the intersection of social justice work with education in the visual arts, music, theatre, dance, and literature. Weaving together resources from a range of University of Illinois Press journals, the editors offer articles on the scholarly inquiry, theory, and practice of social justice arts education. Selections from the past three decades reflect the synergy of the diverse scholars, educators, and artists actively engaged in such projects. Together, the contributors bring awareness to the importance of critically reflective and inclusive pedagogy in arts educational contexts. They also provide pedagogical theory and practical tools for building a social justice orientation through the arts.